Women Empowerment in Indian Apparel Industry through CSR Activities: An Impact Analysis - Pawar, Bhuvanesh (Digital Repository of Theses, 2025)
Women’s economic empowerment, particularly within India’s apparel sector, remains a vital subject of inquiry, given the industry's large female workforce and its potential to contribute to gender equality. While employment in the apparel sector offers women avenues for financial independence and social mobility, the sector also presents structural challenges including gender discrimination, unequal pay, and limited leadership roles. Although Corporate Social Responsibility (CSR) initiatives have been increasingly implemented to promote women’s empowerment, there remains a notable research gap in evaluating the effectiveness, sustainability, and inclusivity of these efforts. The aim of this study is to analyze the impact of CSR initiatives on women's empowerment in the Indian apparel industry. Using a quantitative research design, primary data were collected through survey questionnaires from 300 participants, supported by secondary data from company reports and policy documents. The results highlight that while many firms undertake CSR initiatives aimed at health, skill development, and workplace safety for women, a disconnect often exists between policy and implementation. The study proposes a framework for measuring CSR effectiveness based on educational access, leadership development, equal pay, and workplace inclusivity. These findings have significant implications for CSR policymakers, apparel sector leaders, and gender advocacy groups aiming to align business objectives with sustainable development goals. The originality of this research lies in its comprehensive evaluation of CSR’s role in bridging gender gaps and promoting sustainable, inclusive growth within India’s largest industrial employer of women. Keywords - Women’s Empowerment, Apparel Industry, Corporate Social Responsibility, Gender Equality, India, Workplace Inclusivity, Economic Empowerment, Gender Discrimination, CSR Impact Framework, Female Workforce